11(t-6)+4t=5(3t+2)-9

Simple and best practice solution for 11(t-6)+4t=5(3t+2)-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11(t-6)+4t=5(3t+2)-9 equation:


Simplifying
11(t + -6) + 4t = 5(3t + 2) + -9

Reorder the terms:
11(-6 + t) + 4t = 5(3t + 2) + -9
(-6 * 11 + t * 11) + 4t = 5(3t + 2) + -9
(-66 + 11t) + 4t = 5(3t + 2) + -9

Combine like terms: 11t + 4t = 15t
-66 + 15t = 5(3t + 2) + -9

Reorder the terms:
-66 + 15t = 5(2 + 3t) + -9
-66 + 15t = (2 * 5 + 3t * 5) + -9
-66 + 15t = (10 + 15t) + -9

Reorder the terms:
-66 + 15t = 10 + -9 + 15t

Combine like terms: 10 + -9 = 1
-66 + 15t = 1 + 15t

Add '-15t' to each side of the equation.
-66 + 15t + -15t = 1 + 15t + -15t

Combine like terms: 15t + -15t = 0
-66 + 0 = 1 + 15t + -15t
-66 = 1 + 15t + -15t

Combine like terms: 15t + -15t = 0
-66 = 1 + 0
-66 = 1

Solving
-66 = 1

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -16x^5-44x^4+30x^3=0 | | -3=x/6-6 | | 9x-(8x+2)=2x-40 | | 12-6x=3x-3 | | 6m+3(2m+5)+7=0 | | 6=n-8 | | -2AH=V^2-U^2 | | 28+3p=-4p | | x-2y^2-8y=3 | | 19x-4=10x-40 | | x-3/3=41/2 | | 4x-5x+x-7+2x= | | 4-3Y=30 | | 7x+8-x=35 | | 20=-12+u | | -1=r/4-2 | | -3z-7z+4=0 | | 2n^4+16n^2+21=x | | 63w-44-47w=-140 | | x-8y-2y=3 | | 0.20x=46 | | (2x+3)/5=9 | | 1-9x=0 | | (5y+5)-(2+4y)=9 | | 6x+7(2x-17)=41 | | 3(4x+6)=-35+41 | | 3x-2/5=x-2 | | b/9+1/4=11 | | 2x-6x-65=63 | | 3(2x+9)=5(x-2) | | 2AH=V^2-U^2 | | 6x-50=10x+73 |

Equations solver categories